Synthesis and structural properties of diamineplatinum(II) and diamineplatinum(IV) complexes of alkylidenemalonic acids - Jung, CS; Lee, SS; Jung, OS; Sohn, YS (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
New diamineplatinum(II) complexes of alkylidenemalonate ligands, A(2)Pt(OOC)(2)C=CR(2) [A(2) = ethylenediamine (en), propylenediamine (pn); R(2) = 2CH(3), (CH2)(5)] have been prepared. Subsequent oxidation of the complexes with H2O2 leads tothe corresponding dihydroxyplatinum(IV) complexes, cis,cis,trans-A(2)Pt((OOC)(2)C=CR(2)) (OH)(2). Among the octahedral complexes, cis,cis,trans-(pn)Pt((OOC)(2)C=C(CH3)(2))(OH)(2) and cis,cis,trans-(pn)Pt((OOC)(2)C=C(CH2)(4)CH2)(OH)(2) have been characterized by X-ray crystallographic analysis. The local geometry of the platinum(IV) atoms is approximately octahedral with hydroxide groups in trans positions. The boat conformation of the chelated dicarboxylate ring in platinum(IV) complexes is less bent than that of the corresponding platinum(II) analogues. Carboxylation of the hydroxide of A(2)Pt((OOC)(2)C=C(CH3)(2))(OH)(2) with acetic anhydride affords A(2)Pt((OOC)(2)C=C(CH3)(2)) (OAc)(2) (A(2) = en, pn), whereas the reaction of A(2)Pt((OOC)(2)C=C(CH2)(4)CH2)(OH)(2) under the same conditions does not produce the corresponding analogue. NMR spectra indicate that the structures of the title complexes are retained in aqueous solution.
Keywords: PLATINUM ANTICANCER DRUG; MOLECULAR-STRUCTURE; CRYSTAL; METABOLITE; DNA